The Role of King Khalid University in Developing Women Leaders - Mubarky, Maryam Mohammd (Journal of Economic, Administrative and Legal Sciences, 2020)
Women are one of the most important contributors to development. In all international and local organizations, in addition to civil society institutions, womanly part of the human society has taken an active role in the development process. The field of education is the primary field of interaction with society. It plays an outstanding role in developing feminine personal. This stands on a sound and solid basis, guiding, hereto, a bursting capacity through continuous training and practice. Such a practice is analyzed in this paper to prove its efficiency in the case of KKU feminine personal. The research problem is formulated to praise high the role played by King Khalid University in the advancement of the woman leadership in the university. It is formulated to answer one main question: How does a university academic activity in KKU contribute in building female leadership capacity in the case of female teaching staff? The research aims to employ the development of the female lead in the university and then to highlight the role of the university in developing. An investigative approach, through both descriptive and statistical analysis, is used to achieve the research objectives. The research is based on the individual interviews of a sample of the feminine leaders at the university. A questionnaire, based on random sampling, was distributed among female leaders in King Khalid University Staff members.